PELUANG NON-FUNGIBLE TOKEN SEBAGAI MEDIA APRESIASI SENIMAN LOKAL BANDUNG - Aryasatya Rafa Prayitno; Luthfi Baihaqi Riziq; Rizqi Vazrin; Caroline Natasha Amartya Wawor; Janaka Isnan Daru (POLITEKNIK LP3I JAKARTA, 2023)
Indonesian Central Agency on Statistics notes the decline of national economic status by 2,07% in 2020 and Dewi, on the same year, reported its effect to the world of art and painting investments. This research carry that problem and tries to look at Non-Fungible Token (NFT) as an advanceable means to increase artists’ economic welfare, especially after the NFT trend at the start of 2022. Specifically, this research focuses on artists found on Braga Street, Bandung City, as a first step in exploring the opportunity of NFT in increasing economic welfare. This article aims to analyze and formulating the potential of NFT in increasing artists’ economic welfare by way of in-depth interview as the main method.Key words: NFT, Local Artists, Bandung, Economic Welfare